1994
DOI: 10.1139/v94-061
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of D-gluconic acid by chromium(VI) in perchloric acid

Abstract: The oxidation of gluconic acid by chromium(VI) in perchloric acid has been found to follow the rate law: −d[CrVI]/dt = (k′1 + k′2[GA])[H+]2[CrVI], where k′1 = (7.1 ± 0.2) × 10−4 M−2 s−1 and k′2 = (9.4 ± 0.2) × 10−2 M−3 s−1. This rate law corresponds to the reaction leading to the formation of 2-ketogluconic acid by C—H cleavage when a 20-fold or higher excess of acid over chromium(VI) is employed. Buildup and decay of chromium(V) intermediates accompany the decay of chromium(VI). Chromium(V) rates of decay are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“…Our studies on the reduction of Cr VI and the intermediate Cr V by aldoses (21)(22)(23)(24)(25)(26), deoxyaldoses (27)(28), sugar acids (31,32,35), and methyl glycosides (29)(30) showed that the relative redox reactivities of these saccharides toward chromate are based on the relative rates of the oxidation vs. complexation processes. In view of some preliminary results obtained on the milk-Cr VI system suggesting the formation of long lived lactose-Cr V species generated by direct reaction of Cr VI with lactose (5), we decided to evaluate the kinetics of the reaction of Cr VI with four disaccharides: D-lactose (Lac), D-maltose (Mal), D-cellobiose (Cel), and D-melibiose (Mel), to determine the influence of the glycoside moiety attached to the C 6 or C 4 of glucose (glc) on the chelating and (or) redox reactivity of the saccharide with high oxidation states of chromium.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Our studies on the reduction of Cr VI and the intermediate Cr V by aldoses (21)(22)(23)(24)(25)(26), deoxyaldoses (27)(28), sugar acids (31,32,35), and methyl glycosides (29)(30) showed that the relative redox reactivities of these saccharides toward chromate are based on the relative rates of the oxidation vs. complexation processes. In view of some preliminary results obtained on the milk-Cr VI system suggesting the formation of long lived lactose-Cr V species generated by direct reaction of Cr VI with lactose (5), we decided to evaluate the kinetics of the reaction of Cr VI with four disaccharides: D-lactose (Lac), D-maltose (Mal), D-cellobiose (Cel), and D-melibiose (Mel), to determine the influence of the glycoside moiety attached to the C 6 or C 4 of glucose (glc) on the chelating and (or) redox reactivity of the saccharide with high oxidation states of chromium.…”
Section: Introductionmentioning
confidence: 83%
“…We are studying the possible fate of Cr VI and Cr V in biological systems by examining reactions of Cr VI with low-molecular-weight molecules (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37). Our studies on the reduction of Cr VI and the intermediate Cr V by aldoses (21)(22)(23)(24)(25)(26), deoxyaldoses (27)(28), sugar acids (31,32,35), and methyl glycosides (29)(30) showed that the relative redox reactivities of these saccharides toward chromate are based on the relative rates of the oxidation vs. complexation processes.…”
Section: Introductionmentioning
confidence: 99%
“…This is why, it is not possible to discriminate between these two mechanisms kinetically. However, the Rocek mechanism is now widely accepted to explain the Cr(VI) oxidation of varieties of organic substrates [60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76]. Some authors have suggested the simultaneous operation of both the schemes depending on the conditions [2,77].…”
Section: The Common Pathways Leading To Reduction Of Chromium(vi) To mentioning
confidence: 99%
“…The ligands like 2-hydroxyacids, diols, sugars, etc. possessing two oxygen atoms capable of forming the five membered rings about the metal center are quite important to stabilize the hypervalent oxidation states of chromium [1,2,14,15(a), 42,[46][47][48]61,62,65,66,69,71,73,74]. Amino acids and peptides can also stabilize these states [88,89].…”
Section: The Common Pathways Leading To Reduction Of Chromium(vi) To mentioning
confidence: 99%
“…Our studies on the reduction of Cr VI and intermediate Cr V by aldoses [20] [30] [31] [33], deoxyaldoses [20] [23] [25] [30] [31], sugar acids [22] [27] [29], and methyl glycosides [34] showed that the relative redox reactivities of these saccharides toward chromate is based on the relative rates of the oxidation vs. complexation processes [31] [32]. Under conditions of excess reductant over Cr VI , aldoses, deoxyaldoses, and sugar acids are selectively oxidized at OHÀC (1), and in methyl glycosides, where the anomeric position is blocked, the oxidation takes place at OHÀC (6).…”
mentioning
confidence: 99%